Entrepreneurial Passion in Social entrepreneurs in Czech Republic - Balgiashvili, Tamar; Andera, Michal, 1984-; Brunet-Thornton, Richard; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2017)
Social Entrepreneurship has become a buzzword due to exponentially rising number of scientific works devoted to this topic. The prevalent part of the research focuses on the social side of the venture, while the other equally important entrepreneurial side is still in the shadow. Can it be that social entrepreneurs do not value the entrepreneurial aspect (inventing, founding and developing) od social entrepreneurship and are engaged in these activities only because of other goals and passions (for example “helping”, “social welfare” etc.). The first research question aligns with the existing research about dividing the social and commercial entrepreneurs according to their goal priorities, while answering the second research question brought us to the new discoveries regarding the “entrepreneurial” side of the social entrepreneurial venture, particularly examining the passion for inventing, founding and developing. Research found that there is no significant difference in term of entrepreneurial passion between social and commercial entrepreneurs. Moreover, we confirm that while the difference is goal orientation is valid, the boarders between social and commercial entrepreneurs are rather blurred.
Vedoucí práce: Michal Andera
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor dipl. práce]; diplomové práce; master's theses